2014
DOI: 10.17219/acem/37019
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Theophylline on the Prevention of Mechanical Ventilation-Induced Diaphragm Atrophy in Rats

Abstract: Background. Movement disorders and atrophy occur in the diaphragm, the most important muscle of respiration, because of mechanical ventilation (MV). Objectives. In this animal model, we aimed to evaluate the effect of intravenous theophylline administration on the prevention of mechanical ventilation-induced diaphragmatic atrophy. Material and Methods. In our study, 30 healthy male Sprague-dawley rats were used. They were divided into 3 equal groups. Group 1: the control group (no MV); group 2: the placebo gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In previous studies, we found that Bufei Jianpi granules can significantly improve lung function, reduce frequency and extent of acute exacerbations, prolong six-minute walk distance and improve quality of life and have beneficial long-term effects after a 12-month follow-up in COPD patients; and improve pulmonary function and increase diaphragm muscular tension and endurance in cigarette-smoke and Klebsiella pneumoniae induced COPD rats [ 17 , 18 ]. Aminophylline is a complex of theophylline and ethylenediamine, which is not only a bronchodilator, but also with pharmacological actions in alleviating inflammatory response and improving the function of diaphragm and peripheral skeletal muscles [ 19 - 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we found that Bufei Jianpi granules can significantly improve lung function, reduce frequency and extent of acute exacerbations, prolong six-minute walk distance and improve quality of life and have beneficial long-term effects after a 12-month follow-up in COPD patients; and improve pulmonary function and increase diaphragm muscular tension and endurance in cigarette-smoke and Klebsiella pneumoniae induced COPD rats [ 17 , 18 ]. Aminophylline is a complex of theophylline and ethylenediamine, which is not only a bronchodilator, but also with pharmacological actions in alleviating inflammatory response and improving the function of diaphragm and peripheral skeletal muscles [ 19 - 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…② In MV, the physiological negative thoracic pressure becomes positive, cardiac output decreases, and diaphragmatic blood flow reduces. Theophylline also facilitates diaphragmatic perfusion by improving cardiac output and providing vasodilation in diaphragmatic arterioles [ 96 ]. ③ During MV, many inflammatory factors (e.g., interleukin [IL]-6, IL-1β, and tumor necrosis factor-α) are activated.…”
Section: Prevention and Treatment Measuresmentioning
confidence: 99%
“…Conessine, a steroidal alkaloid, reduces dexamethasone-induced muscle atrophy by downregulating the expression of MuRF1 and MAFbx in C2C12 myotubes [138]. Theophylline reverses the muscle atrophy induced by 28 weeks of cigarette smoke exposure via suppressing the inflammatory effect, upregulating histone deacetylase 2 expression, and inhibiting the activation of NF-κB and p65 in Kunming mice model [139,142]. TGF-β, a classical modulator of skeletal muscle, regulates several processes in skeletal muscle disease including inhibition of myogenesis, diminution of regeneration, and induction of muscle atrophy.…”
Section: Alkaloidsmentioning
confidence: 99%